Cloud computing security : foundations and challenges - Vacca, John R., 1947- (CRC Press, 2017)
This handbook offers a comprehensive overview of cloud computing security technology and implementation, while exploring practical solutions to a wide range of cloud computing security issues. With more organizations using cloud computing and cloud providers for data operations, proper security in these and other potentially vulnerable areas have become a priority for organizations of all sizes across the globe. Research efforts from both academia and industry in all security aspects related to cloud computing are gathered within one reference guide. - Resumé vydavatel
Keywords: cloud computing; počítačové sítě; ochrana dat; počítačová bezpečnost; computer networks; data protection; computer security; příručky; elektronické knihy; handbooks and manuals; electronic books